Differences in self-regulatory skills among talented athletes: The significance of competitive level and type of sport - Jonker, L.; Elferink-Gemser, M. T.; Visscher, C. (Journal of Sports Sciences, 2010)
Research has shown that talented athletes outscore their mainstream peers on the basis of self-regulation. Although valuable, this does not tell us more about the distinction between good athletes and the best, which is a prerequisite in talent development. Therefore, we examined the self-regulatory skills of 222 male and female talented athletes aged 12-16 years as a function of competitive sport level (junior international or junior national athletes) and type of sport (individual or team sports). Multivariate analyses of covariance in combination with a discriminant function analysis revealed that "reflection" distinguishes between athletes at the highest levels of excellence. Furthermore, athletes playing individual sports had higher scores on "planning" and "effort" than team sport athletes, highlighting the importance of differences between types of sport. In conclusion, we emphasize the importance of reflection as a self-regulatory skill. Reflection facilitates the development of sport-specific characteristics, which may vary by type of sport. This means that an advanced sense of reflection may help talented athletes to acquire desirable characteristics during their "talent" years to ultimately reach adult elite levels of competition.